Atlas of the world's deserts - Harris, Nathaniel (Fitzroy Dearborn, 2003)
The Atlas of the World's Deserts examines the hostile and extreme environments that characterize deserts, and is divided into chapters that concentrate on specific aspects of a desert's geology, life forms, history, and future.